Pengaruh Kualitas Audit, Struktur Kepemilikan Manajerial Dan Profitabilitas Terhadap Manajemen Laba Dengan Intellectual Capital Sebagai Variabel Moderating - Mughfirotul Makhfiyah; Suwarno Suwarno (Economics and Digital Business Review, 2023)
This study aims to examine the effect of audit quality, managerial ownership in manufacturing companies listed on the Indonesia Stock Exchange in 2022 with a total of 225 companies. The sampling technique used purposive sampling. Samples that met the criteria in this study were used by 76 companies. Data management for the study was carried out using SmartPLS 4 software. The research results show that : (1) quality audit have no effect on earnings management, (2) managerial ownership structure have no effect on earnings management, (3) profitability affect earnings management, (4) intellectual capital are not able to moderate the effect of quality audit on earnings management, (5) intellectual capital are not able to moderate the effect of managerial ownership structure on earnings management, (6) ) intellectual capital are not able to moderate the effect of profitability on earnings management.